ANALISIS INDEKS KEPUASAN MASYARAKAT BAGI PESERTA ASKESKIN DI PUSKESMAS PADANGSARI SEMARANG - Ramawinata, A. Mesa; Hidayat, Zaenal; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This study aims to analyze quality of service provided to the public Semarang Padangsari clinic / community. Analyze the extent to which level of satisfaction towards the services provided by the clinic Padangsari Semarang. Analyze the suitability of performance clinic with hopes of serving the interests of society or the level of service usage PHC services Padangsari Semarang. The samples were accidental sampling. The sample in this study of 150 respondents. Data analysis techniques using the value of Community Satisfaction Index (IKM)Findings of the research results show that the overall performance quality of service for the use of community health centers serving Padangsari Semarang services can be categorized properly. However, some aspects still need to be improved, although some other aspects has shown good performanceSome aspects of the performance has been good among others: Procedures, Care Requirements, Disciplinary Officer Service, Courtesy and Hospitality Officer, Fairness Care Costs, Cost Certainty and Assurance Services Services ScheduleThen some other aspects that still need to be improved performance include: Clarity Services Officer, Services Officer Responsibilities, Capabilities Services Officer, Service Speed, Obtain Justice Services, Environmental Comfort and Security Services